A comparison of model prediction from P2D and particle packing with experiment. (20th February 2021) - An, Fuqiang; Zhou, Weinan; Li, Ping
Abstract: Design and optimization of the microstructure of the lithium-ion cell electrode is the key to improving its rate capability after the type and particle size of the active materials are fixed. The P2D electrochemical model, although widely-utilized, has limitation for this purpose due to its homogeneous description of the electrode particles and pores. Conversely, the particle packing model, which is capable of describing the spatial and size distributions of active particles, as well as the conductive network between them, offers new potential. In this work, for electrode designs with different areal/press densities, we compare the predictions from the P2D model and particle packing model with experiments. It is shown that the simulated rate discharge performance of the particle packing model fits well with the experimental tests, while the predictions of the P2D model show ambiguities and inadequacies at a high discharge rate (2C). Tortuosity, which is an important characteristic parameter of pore structure, has been investigated to correct the accuracy of P2D models, and the fitted values calculated from the particle packing model and experimental measurement are compared. In addition, we compare the difference of the lithium ion concentration distribution inside the electroactive particles and electrolytes between the P2D model (pseudo two-dimensional and homogeneous) and the particle packing model (two-dimensional and heterogeneous).